Developing Management Application for State Properties at State Islamic Institute of Palopo - Diah Asdiany; Khaidir Mubarak Putrasyam; Dodi Ilham (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to: (1) Obtain an information system for monitoring the use of State-Owned Goods inventory at IAIN Palopo (2) The system built can be a solution in managing and monitoring the use of State-Owned Goods inventory. The type of research used is Research and Development (R & R&D), with the Waterfall Model development model consisting of five stages, namely Requirement Analysis and Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, and Operation maintenance. The results of this study are in the form of an information system that can facilitate data management and monitoring the use of State Property at IAIN Palopo.